Diversity of Gut Microbiota and Bifidobacterial Community of Chinese Subjects of Different Ages and from Different Regions - Yang, Bo; Yan, Shuang; Chen, Yang; Ross, R. Paul; Stanton, Catherine; Zhao, Jianxin; Zhang, Hao; Chen, Wei (Microorganisms (Basel), 2020)
Gut microbiota composition and functionality are closely linked to host health. In this study, the fecal microbiota and bifidobacterial communities of 111 healthy volunteers from four regions of China of varying age profiles (Child, 1–5 years; Young, 18–50 years; Elder, 60–80 years; Longevity, ≥90 years) were investigated via high-throughput sequencing. Canonical analysis revealed that the gut microbiota, as well as bifidobacteria profiles of the subjects, clustered according to their regions and age. Eight genera were shared among all subjects, however, certain genera distributed differently in subjects grouped by region and age. Faecalibacterium was enriched in samples from Zhongxiang, unclassified Ruminococcaceae and Christensenellaceae were enriched in the Longevity group, and Bifidobacterium was enriched in Child. Within Bifidobacterium, B. longum was the most abundant species in almost all samples except for Child, in which B. pseudocatenulatum was the most abundant. Additionally, the abundances of B. adolescentis and B. dentium were lower in Child. In conclusion, our results suggest that geography and age affect the structure of the gut microbiota, as well as Bifidobacterium composition, and this variation may greatly associate with the metabolic and immune changes that occur during the process of aging.